2023
DOI: 10.3390/diagnostics13091623
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiomics in Fibrosis Crohn’s Disease: A Review

Abstract: Inflammatory bowel disease (IBD) is a global health concern that has been on the rise in recent years. In addition, imaging is the established method of care for detecting, diagnosing, planning treatment, and monitoring the progression of IBD. While conventional imaging techniques are limited in their ability to provide comprehensive information, cross-sectional imaging plays a crucial role in the clinical management of IBD. However, accurately characterizing, detecting, and monitoring fibrosis in Crohn’s dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…MSCT not only aids in the detection and localization of fibrotic lesions but also assists in assessing the extent and complications associated with fibrosis, such as strictures and fistulas 36 . The use of MSCT in fibrosis evaluation in IBD offers several advantages, including its non-invasive nature, widespread availability, and ability to provide detailed anatomical information 12 . In this study, a nomogram was developed to predict fibrosis in IBD by integrating radiomics score, engorged vasa recta, AP-CT value, and lesion location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCT not only aids in the detection and localization of fibrotic lesions but also assists in assessing the extent and complications associated with fibrosis, such as strictures and fistulas 36 . The use of MSCT in fibrosis evaluation in IBD offers several advantages, including its non-invasive nature, widespread availability, and ability to provide detailed anatomical information 12 . In this study, a nomogram was developed to predict fibrosis in IBD by integrating radiomics score, engorged vasa recta, AP-CT value, and lesion location.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics, a rapidly evolving field in medical imaging, has gained significant attention in various clinical domains, where it has shown great potential for predicting treatment response, prognosis, and even guiding personalized therapies 11 . Radiomics refers to the extraction of a large number of quantitative imaging features from medical images, followed by the application of advanced data analysis techniques 12,13 . These features capture the heterogeneity and spatial patterns of tissues, enabling a more comprehensive and objective characterization of disease processes 14 .…”
mentioning
confidence: 99%
“…The study demonstrated a high level of agreement between the measurements obtained through semi-automated analysis and those conducted by experienced radiologists [ 77 ]. Consistent with findings in other diseases, a limited number of studies have indicated that radiomics of MRE and CTE, which involves extracting high-dimensional data from cross-sectional imaging, hold promise as a valuable source of information for evaluating fibrosis in IBD [ 74 , 75 ].…”
Section: The Role Of Artificial Intelligence (Ai) Alongside Molecular...mentioning
confidence: 89%
“…This approach has been employed to enhance effective decision-making pertaining to treatment options. It been also applied to detect fibrosis CD [ 74 ]. Radiomic models were developed which provided significantly greater accuracy in characterizing enteric fibrosis than human radiologist capability in CD patients [ 75 ].…”
Section: The Role Of Artificial Intelligence (Ai) Alongside Molecular...mentioning
confidence: 99%
“…Interestingly, promising perspectives come from advanced technologies, namely radiomics. Radiomics consists of extracting quantitative data from medical images to use them to create machine-learning algorithms able to predict outcomes of interest [ 77 ]. It found its first applications in the field of oncology; however, in recent years, radiomics has assumed a more significant role even in IBD, standing out as a decision-supporting tool in clinical practice.…”
Section: Computed Tomography Enterography and Radiomicsmentioning
confidence: 99%